The cost-effectiveness of a home-based exercise programme for the treatment of knee pain in the community - Thomas, Kim Suzanne (2001)
Objectives: o To determine the prevalence of knee pain in the population aged ≥45 years. o To determine the benefit or otherwise of regular home exercise and telephone contact in reducing the burden of knee pain in the community. o To determine the economic burden of knee pain from a societal perspective. o To determine the cost-effectiveness and cost-utility of the compared interventions.